MARKETING MODEL OF STARBUCKS: A SUSTAINABILITY MONETIZATION - Daniel Susilo; Carlo Magno T. Mendoza (SEAN Institute, 2023)
In the digital age, big brand provides information via their Instagram account, that includes Starbucks Indonesia. Starbucks Indonesia involves themselves in eco-friendly product which also spread awareness to their audience. As much as it is good for the people and Starbucks brand, this type of marketing is sustainability monetization as it only released product instead of social activity. It is good that Starbucks Indonesia had credibility in coffee industry. However, in reality, it is more necessary to monetize it. The content analysis by Krippendorf will help in discerning Starbucks Indonesia’s content. the type of sustainability campaign held by Starbucks Indonesia is monetization of eco-friendly concept. This way can be interpreted in two different ways, that the product is actually made with eco-friendly design and ingredients, or the product is bait made with false sustainability products. The model of their marketing is awareness-driven interest, by telling them they’re the ally of earth and nature, it captivates their buyers to purchase in order to care more for the planet and nature.